Structural behavior of joined hemispherical-cylindrical air-supported membrane structure under vertical loading deflation. Issue 3 (February 2020) - Qing, Qiang; Guo, Xiao; Gong, Jinghai; Li, Zhongli
The structural behavior of an air-supported structure with long span and large volume probably experiencing severe deflation in a massive snow weather deserves in-depth assessment study for occupant's safe evacuation. This article presents experimental and numerical studies on the loading deflation process of a 1:10 scale joined hemispherical-cylindrical air-supported structure, whereby three different sandbag loadings were respectively applied on the hemisphere in each test to study the effect of vertical loads to collapse process. Numerical models based on the vector form intrinsic finite element method were employed to predict the deflation responses of the structure under the three loading cases. The structural behavior was evaluated by the pressure response, the wrinkling distribution and development, and the structural collapse mode. A comparison of their pressure responses and structural deflated forms is made to evaluate the contribution of external loading to the deflation progress and the collapse mode. It is found that the pressure will decrease quickly first and then remain relatively stable at a higher level in response to a larger vertical load in addition to the membrane weight. Due to pressure reduction during deflation, the structure loses tension stress in vertical direction so that vertical wrinkles develop in addition to local wrinkles due to external loading. The vertical loading determines distribution of wrinkles in the structure hence produce different collapse progresses for the three loading deflation cases, and accordingly changes the residual pressure it needs to hold its deflated form. Accordingly, the study proposes a feasible method for residual pressure estimation by identifying the distribution of critical residual pressures at different heights from the equilibrium equation of vertical forces. The full-scale structure presents similar structural behaviors when subjected to snow loading deflation, and the feasible method is valid to predict its residual pressure.